ISOLAT-ISOLAT KHAMIR DARI MINUMAN TRADISIONAL LARU DI NTT [Yeast Diversity Deprived from Laru, a Traditional East Nusa Tenggara Drink] - Rahmansyah, M; Kanti, A (BERITA BIOLOGI, 1999)
Sixteen isolates of yeast were collected from Law fa fermented palm sap or syrup which were tapped from palm infbrescence stalk of Borassus flabellifer L). Physiological performances were tested according to Bamett method for assimilation of some sources of carbon, nitrogen and cycloheximide. Based on the percentage of discrepancy, 6 isolates have been identified. The isolates were respected in high analogical affinity and identified as Arxula adeninovoras (93%), Lipomyces tetraspows (100%), Rhodotorula mucilaginosa (97%), Saccharomyces cerevisae (95%), Schwanniomyces occidentalis var. occidentalis (96%) and Pichia anomala (99%). The yeast that usually found in food fermentation was P. anomala, R. mucilaginosa and S. cerevisiae. The others yeast have great opportunity as indigenous ones.